A new genus and species of bee-mimicking clearwing moths from Mozambique (Lepidoptera: Sesiidae: Sesiini) - Bartsch, Daniel; Bakowski, Marek (Zootaxa, 2026)
This article provides a description of a new genus and species of Sesiini, Osmiasphex gorongosus gen. nov. & sp. nov., from central Mozambique. The new genus is characterized by an unusually short and broad head, with short, clavate antennae and short labial palpus with a greatly reduced terminal segment. It appears to be a mimic of bees of the genus Osmia Panzer, 1806.